Assessment and aftercare for deliberate self-harm patients provided by a general hospital psychiatric service. - Haw, C; Hawton, K; Whitehead, L; Houston, K; Townsend, E (2003)
We report on a sample of 135 deliberate self-harm (DSH) patients who were assessed by a general hospital DSH service, and on those who were offered aftercare by, or telephone open access to, the service. Patients' satisfaction with assessment and treatment, and their outcome were investigated at follow-up 12-20 months later. Four-fifths of patients reported the assessment following DSH to have been helpful and the assessor sympathetic. Thirty-three (24%) of the 135 patients assessed were offered treatment by the DSH service but 13 declined or failed to attend. Of the 20 who engaged in treatment, 17 (94%) were satisfied with their care. Open access to the DSH service by telephone was offered to 53 (39%) patients, nine (22%) of whom reported at follow-up that they had used this facility. A specialist DSH service can effectively assess and treat patients following DSH. It is important that the service is accessible and acceptable to patients.